Multi-criteria Overlay Analysis for Identifying Preferred Exploration Zones on Mars - Yousef Mashal; M. Ramy El-Maarry; M. Pajola; Ioannis Kourakis (The Planetary Science Journal)
Selecting sites for future human and robotic missions to Mars requires the integration of diverse data sets. A variety of global data sets have been exploited, including geological, mineralogical, and topographical. This study utilizes a Geographic Information System based Multi-Criteria Overlay Analysis technique to identify optimal exploration zones on Mars. A set of criteria were built according to both scientific objectives and engineering constraints proposed by the Mars Exploration Program Analysis Group. The resulting composite maps highlight regions that meet both scientific and in situ resource utilization criteria, as well as engineering constraints. The proposed regions are within midlatitudes, are at low elevation, and display moderate to high thermal inertia. Further examination of the map generated using different methods has enabled us to refine these selections based on the availability of resources like water ice and the previously proposed landing sites. A total of 23 regions identified held the highest statistical score, which we suggest merits further in-depth analysis. This technique allows for a flexible and scalable methodology that can be adapted as new data sets become available, thus continuously offering refined site recommendations.